Effects of vibrotherapy on electric activity of fatigued muscles in professional basketball women players - Rodriguez, V.; Lopez, A. F.; Moreno, C.; Abecia, C.; Seco, J. (Archivos de medicina del deporte, 2008)
Throughout recent years different mechanical devices have been designed in order to help sport players` recovery. The scope of this study was assess the efficiency of a mechanical device that generates vibrations (vibrotherapy) in lower extremities, on fatigued muscle in professional basketball players. Material and methods: Subjects: 12 professional basketball women players (22,5 ± 5,0 years old, 79,5 ± 7,8 kgs., 177,5 ± 7,0 cms.). Material: MRM®vibrotherapy device was used. It generates rhythmic moves in lower extremities at a frequency of 3,4 Herzts during 6 minutes. Also, a surface electromyograph MEGA (Muscle Tester ME 3000, 8 channels, software Megawin 2.1 version). Method: patient is sat down with knee bent up to 45º, and is asked to do a maximum isometric contraction of right leg (10 seconds) both pre and post vibrotherapy application during 6 minutes. Afterwards the electrical activity of vastus medialis and biceps femoris was analysed through surface electromyography, during maximum isometric contraction pre and post vibrotherapy application. Statistical Analysis: it was made through the Wilcoxon test. Results: Electric activity of treated muscles increases after vibrotherapy application (p<0,05). Conclusions: Vibrotherapy with MRM®device at a frequency of 3,4 Hertzs, increases the electric activity of treated muscles in professional basketball women players.Deskriptoren